Feed-in tariff for Solar Photovoltaic: The Rise of Japan - Firdaus, Muhammad-Sukki; Siti Hawa, Abu Bakar; Abu Bakar, Munir; Siti Hajar, Mohd Yasin; Roberto, Ramirez-Iniguez; Scott, G. McMeekin; Brian, G. Stewart; Narbin, Sarmah; Tapas, Kumar Mallick; Ruzairi, Abdul Rahim; Md. Ershadul, Karim; Salman, Ahmad; et al. (Elsevier, 2014)
Japan started implementing a national Feed-In Tariff (FiT) mechanism on the 1st July 2012, which included specific payment tariffs for solar photovoltaic (PV) installations. This marks a new era in the renewable energy landscape in Japan. This paper aims at analysing the solar PV prospect in Japan, particularly in both residential and non-residential sectors. The paper presents, first, an overview of energy trends in Japan prior to the Fukushima event. This is followed by a short review of solar PV progress in the country, highlighting the major policies and programmes that have been implemented as well as the installations that have been carried out over the past two decades. Next, the financial impact of the new FiT scheme on consumers is evaluated. The financial analysis investigates the total profit, the average annual return on investment and the payback period. For a comparison purposes, a similar financial analysis is also conducted with selected countries around the world – namely Germany, Italy and the United Kingdom. The results from this analysis indicate that the new Japanese FiT rate generates a good profit, a moderate annual return on investment and an acceptable payback period, suggesting an increasing trend of solar PV uptake over the next years.